Escola pública e gestão neoliberal: o Procad em Minas Gerais - Chemp, Rubens Felipe (2007)
Minas Gerais State public school s principals training, carried out during the 1990s, trough PROCAD I and PROACD II projects seem to be part of structural and ideological changes produced within the capitalist system at the end of the twentieth century. In the international arena, the 1970 s crises of the capitalist system impelled the U.S. Government to adopt (neo) liberal-type strategies, reaffirming capital s monopolist and financial model, in order to keep the U.S. leverage as a dominant nation. At the national setting, here in Brazil, reforms were introduced during the 1990s, following similar direction and also reinforcing the U.S. parameter and the neo-liberal model. In Minas Gerais State changes were also implemented following similar path, and the PROCAD I and PROCAD II projects are part of colligated actions. The mentioned changes emphasize the educational field, making them in the position of searching for the achievement of a dominant hegemonic character (GRAMSCI). PROCAD I and PROCAD II projects were implemented changing the established publics school s administrative direction as they introduce the business managerial way of administration as the most appropriate. Thus, public school, as an educator of disadvantaged classes can multiply the capitalist managerial model as the new blueprint regarding administration organization and values, endorsing and reaffirming capitalist system and its neo-liberal model.